2021
DOI: 10.1108/apjml-05-2021-0351
|View full text |Cite
|
Sign up to set email alerts
|

The optimal subsidy scheme and technology innovation strategy considering consumers' green premium

Abstract: Purpose This paper investigates how a regulator pursuing social welfare maximization designs an optimal subsidy scheme to stimulate technology innovation in the presence of a consumer green premium. Specifically, the authors solve the following questions: (1) Does the consumers' green premium affect the design of the subsidy scheme? (2) How should the firm choose a green technology innovation strategy under the optimal subsidy scheme? (3) Does technology innovation bring higher social welfare and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Li et al (2019) evaluated green suppliers through multiple consecutive evaluation cycles that will aid a company in effectively managing its key suppliers. Wang et al (2021) investigated the optimal subsidy scheme and technology innovation strategy considering consumers' green premium. Dong et al (2016) further explored the sustainability investment of RPs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al (2019) evaluated green suppliers through multiple consecutive evaluation cycles that will aid a company in effectively managing its key suppliers. Wang et al (2021) investigated the optimal subsidy scheme and technology innovation strategy considering consumers' green premium. Dong et al (2016) further explored the sustainability investment of RPs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Enterprises can reduce emissions and produce more green-differentiated products [ 37 ], thus gaining new market share and improving green competitive advantage [ 38 ]. Consumer’ acceptance of green products with green innovation continues to rise, and they can tolerate the product premium brought about by green products to a certain extent [ 39 ], further expanding the profit space brought about by green innovation. In the face of green-conscious consumers, downstream enterprises producing environmental-friendly products, and upstream enterprises using green technology, the pressure of green market demand forces enterprises to produce green innovation demand [ 40 ].…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Some literature considered R&D at the product level (Hong and Guo, 2019; Agi and Yan, 2020; Wang et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nie et al (2022) found technology spillover reduces the price of innovative products, benefits competitors and damages high-tech companies. Wang et al (2021) considered consumer segments and compared risky internal innovation and risk-free external introduction.…”
Section: Technology Research and Developmentmentioning
confidence: 99%
See 1 more Smart Citation